The critical role of parenting in human development - Klebanov, Marianna S.; Travis, Adam D. (New York, NY : Routledge, Taylor & Francis Group, 2015)
'This thorough and multidisciplinary overview of childrearing illustrates and stands on two foundational principles: that the importance of parenting is immense, and that it is undervalued. The Critical Role of Parenting in Human Development surprises readers with the realization that the way we were parented in childhood impacts nearly every aspect of our lives. Based in part on cutting-edge research using MRI and fMRI technologies demonstrating that the brains of those traumatized in childhood are essentially different, the book explains that our brain development during our earliest years and in the womb is fundamental to the lives we lead.It covers attachment theory, the impact of corporal punishment on the brain, the effects of emotional abuse and neglect, and the widespread nature of Posttraumatic Stress Disorder, describing the process that leads to the transmission of parenting patterns through the generations and explaining how resulting personal issues recur throughout the lifespan. The Critical Role of Parenting in Human Development also examines laws and policies that impact parenting in our culture, making a case for their importance, and describes the effect of childrearing on various aspects of human life, including relationships, crime and violence, economics, mental and physical health, addiction, education, and career issues, among others. Interdisciplinary in nature, this book is a much-needed resource for professionals and students in the psychology, psychotherapy, social work, and related mental health and child welfare fields'--
'The importance of parenting is immense yet undervalued in many Western cultures. As child welfare advocates and mental health professionals know, the first years of life have a tremendous impact on our adult selves, and negative parenting practices, such as corporal punishment, emotional abuse, and neglect, are now shown to have long-lasting effects on an individual's biological, psychological, and emotional development'--
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Parent and child; Parenting -- Psychological aspects; Developmental psychology